PENERAPAN PRINSIP KOMUNIKASI BISNIS PADA AKTIFITAS PERSONAL SELLING SEBAGAI STRATEGI KOMUNIKASI PEMASARAN PEDAGANG PASAR GEDE KOTA SURAKARTA - Novita Haryono; Tulus Haryono (Universitas Tidar, 2024)
Abstract : Traditional markets have an important role in the local economy in Indonesia, including in the city of Surakarta. This traditional market is not only a place for buying and selling transactions, but is also a center of social interaction for local people and also tourists who come from outside the city and abroad. The revitalization of the market and the development of the city of Surakarta as it is today has caused the level of public visits to Pasar Gede to increase. Visitors not only come from local communities but also tourists who come to visit the city of Surakarta. In this research, the research will specifically look at the interactions that occur between sellers and buyers at Pasar Gede as part of a marketing communication strategy, namely personal selling and the application of business communication principles therein. This research was conducted qualitatively descriptively through in-depth interviews with 7 Pasar Gede traders. The results of this research are that traders at Pasar Gede Surakarta understand the importance of business communication principles in their interactions with buyers. Moreover, this interaction is seen as a promotional tool in personal selling. However, this trader has not had further interaction with buyers, such as asking about the quality of after-sales products or providing information regarding new products. Keywords: Personal Selling, Marketing Communication, Business Communication, SME